Forensic psychiatric care professionals’ experiences of communicating with foreign patients and their relatives: the importance of language and culture - Rahman, Omed Abdul; Alexiou, Eirini; Degl’Innocenti, Alessio; Holmberg, Christopher; Olaya-Contreras, Patricia (Frontiers in Psychiatry, 2025)
BackgroundClear and effective communication between patients and professionals in forensic psychiatric care is central to providing accurate information about care and treatment and building trust. Limited language proficiency hinders mutual understanding, making therapeutic interactions significantly more complex. In Sweden, there has been an increase in the number of non-Swedish-speaking immigrants during the last decade, which further emphasizes this important aspect. The aim of this study was to explore the experiences of forensic psychiatric professionals and identify factors influencing effective communication in their interactions with patients and their relatives who have limited proficiency in Swedish.MethodsNine professionals specializing in forensic psychiatry— including physicians, registered nurses, and counselors—participated in deep individual interviews. Qualitative content analysis was conducted inductively, following the Standards for Reporting Qualitative Research.ResultsOne overarching theme emerged—effective communication is the foundation of care and treatment but difficult to separate from culture and translation. Four categories were identified (1): importance of satisfactory communication for effective patient care, (2) challenges and paradoxes of interpreter use, (3) cultural understanding as a guide for deep communication in forensic psychiatry relationships, and (4) health literacy needs of patients and relatives to comprehend treatment.ConclusionTo improve forensic psychiatric care, healthcare providers must adopt structured language assistance measures, such as interpreter services and cultural competency training for professionals. Participants emphasized the importance of integrating cultural awareness in care delivery and ensuring precise communication of complex psychiatric concepts to minimize misunderstandings and enhance patient engagement. Family education and health literacy are crucial in fostering comprehension and optimizing interpreter use, enabling consistent and clear communication. Implementing these measures can lead to a more inclusive healthcare environment, ensuring equal access to mental health services for linguistically diverse patients.